Criminal proceedings : the contemporary American crime novel - Messent, Peter B. (Chicago, Ill. : Pluto Press, 1997)
The American crime novel has never been stronger nor more popular. This exciting new collection offers a comprehensive view of some of the most important developments in crime fiction. The contributors explore the significant new directions which the genre has recently taken and examine their importance in terms of American cultural self-definition as they tap into contemporary concerns about place, identity, gender, race, oppression and justice. In particular, the contributors focus on the ways in which new multicultural perspectives are now challenging the predominantly white, male tradition. The work of some of America's best crime writers is examined, including Patricia Cornwell, James Ellroy, Elmore Leonard, Walter Mosely and Barbara Wilson. The proliferation of sub-genres, such as court and police procedurals, is also examined.
10. Watching the Detectives: Body Images, Sexual Politics and Ideology in Contemporary Crime Film / Brian Jarvis.
Includes bibliographical references.
Keywords: Detective and mystery stories, American -- History and criticism; American fiction -- 20th century -- History and criticism